Monetary Policy, Development of Financial Market and Banking Lending : An Analysis of the Bank-Lending Channel in Malaysia (Malaysian Management Journal, 2001)
Recent resurgence of interest in understanding the transmission mechanism of monetary policy focuses on two main channels of explanation, i.e. the money and credit channel. This paper investigates a version of the credit channel, i.e. the bank-lending channel for the Malaysian economy. The bank-lending channel assigns a critical role for the supply of bank loans in transmitting the effect of monetary policy on real economic activities. The study analyzes the effect of monetary policy on the ability and willingness of Malaysian banks to issue loans with respect to the development in the open financial market. Specifically it argues on the changes of the pattern of influence as progress in the open financial market takes place. A multivariate system analysis of vector auto regression (VAR) is used. The results show that prior to the progress in open financial market, the monetary authority has a direct influence on supply of loans of banks. However, this direct influence lessens as the open financial market develops. Loans are more affected by interest rates spread that dictates conditions in open financial markets. Thus, the ability of the monetary authority to steer real economic activities is subjected to development in the financial market.